2003
DOI: 10.1139/x03-093
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and severity of beech bark disease in the Catskill Mountains, N.Y.

Abstract: Abstract:The distribution and severity of beech bark disease (BBD) in the Catskill Mountains of southeastern New York state, U.S.A., were measured between 1997 and 2000. Forest composition was measured using wedge prism surveys and fixed-area plot counts of canopy species. BBD severity on individual trees was ranked from 1 (no disease) to 5 (dead) based on bark health and canopy loss. These data were analyzed at multiple spatial scales to determine possible controls of disease distribution and severity. BBD wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 17 publications
3
38
1
1
Order By: Relevance
“…3) loss of American beech (Fagus grandifolia) basal area at 732 m is attributable to the invasion of the beech scale (beech bark disease) in the late 1960s, which has killed 80-90% of mature beech trees (27). The highest-elevation American beech (i.e., 792 m) increased in abundance probably because of the limited susceptibility of young trees at low densities to beech bark disease (27,28). Declines of American beech in the lower portions of the ecotone were largely offset by large increases in sugar maple (Acer saccharum) basal area of 60% (6.8 m 2 ha Ϫ1 ) and 115% (2.6 m 2 ha Ϫ1 ) at 732 and 792 m.…”
Section: Resultsmentioning
confidence: 99%
“…3) loss of American beech (Fagus grandifolia) basal area at 732 m is attributable to the invasion of the beech scale (beech bark disease) in the late 1960s, which has killed 80-90% of mature beech trees (27). The highest-elevation American beech (i.e., 792 m) increased in abundance probably because of the limited susceptibility of young trees at low densities to beech bark disease (27,28). Declines of American beech in the lower portions of the ecotone were largely offset by large increases in sugar maple (Acer saccharum) basal area of 60% (6.8 m 2 ha Ϫ1 ) and 115% (2.6 m 2 ha Ϫ1 ) at 732 and 792 m.…”
Section: Resultsmentioning
confidence: 99%
“…2d; results for other common species were qualitatively similar), presumably because the density of small beech has increased so dramatically with BBD. Based on other research, it is clear that in given stands and regions species composition has changed as a possible consequence of BBD (Griffin et al 2003), but at a landscape scale, it appears that beech is predominantly replacing itself. Thus, BBD is altering North American hardwood forests to a condition where trees are of generally smaller stature (because BBD kills mature beech trees) but with no decline in the space occupied by beech.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys in Nova Scotia and Prince Edward Island indicate a frequency of disease-free trees of about 2%, perhaps reflecting intensive exploitation of private woodlots, with removal of many of the undiseased trees. Griffin et al (2003) reported a much lower percentage (0.02%) in the Catskill Mountains of New York State, where the occurrence of the disease is more recent.…”
Section: American Beechmentioning
confidence: 94%
“…It has been detected as far south as West Virginia and west to Ohio. The "killing front" of the disease generally results in high mortality among mature trees (Griffin et al 2003). Seed production is reduced in diseased trees, but root suckers are often abundant, creating an "aftermath forest" characterized by small, heavily damaged trees of clonal and seed origin that may live for decades, before succumbing to the endemic insect-disease complex (Houston 1975).…”
Section: American Beechmentioning
confidence: 99%